Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1631/jzus.b1300006
|View full text |Cite
|
Sign up to set email alerts
|

Identification of miRNAs and their targets in tea (Camellia sinensis)

Abstract: MicroRNAs (miRNAs) are endogenous small RNAs playing a crucial role in plant growth and development, as well as stress responses. Among them, some are highly evolutionally conserved in the plant kingdom, this provide a powerful strategy for identifying miRNAs in a new species. Tea (Camellia sinensis) is one of the most important commercial beverage crops in the world, but only a limited number of miRNAs have been identified. In the present study, a total of 14 new C. sinensis miRNAs were identified by expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 50 publications
(48 reference statements)
1
21
0
1
Order By: Relevance
“…Study carried out in avocado infected with Phytophthora cinnamomi, the most destructive root pathogen of avocado, revealed that cytochrome P450-like TBP (TATA box binding protein) was significantly induced at 3 and 12 h after infection (Mahomed and Berg 2011). Interestingly, cytochrome P450-like TBP was identified as target of miR2911 in Camelia sinensis (Zhu and Luo 2013). Up-regulation of miR2911 was observed in root tissues of orchid Oncidium colonized by the endophytic fungus Piriformospora indica (Ye et al 2014).…”
Section: Addressing the Role Of Microrna-based Regulation In Root-micmentioning
confidence: 99%
“…Study carried out in avocado infected with Phytophthora cinnamomi, the most destructive root pathogen of avocado, revealed that cytochrome P450-like TBP (TATA box binding protein) was significantly induced at 3 and 12 h after infection (Mahomed and Berg 2011). Interestingly, cytochrome P450-like TBP was identified as target of miR2911 in Camelia sinensis (Zhu and Luo 2013). Up-regulation of miR2911 was observed in root tissues of orchid Oncidium colonized by the endophytic fungus Piriformospora indica (Ye et al 2014).…”
Section: Addressing the Role Of Microrna-based Regulation In Root-micmentioning
confidence: 99%
“…Among the other genomic resources, while Kamunya et al (2010) identified 23 minor QTLs, approximately 250 polymorphic SSR markers were validated by various groups (Kato et al 2008, Sharma et al 2009). Apart from that, a few SNPs ) and microRNAs of tea (Das and Mondal 2010;Prabu and Mandal 2010;Mohanpuria and Yadav 2012;Zhu and Luo 2013) had also been identified.…”
Section: Genomic Resourcesmentioning
confidence: 99%
“…There is currently a focus on the microRNAs of tea plants. Some conserved miRNAs have been predicted based on sequence homology with full length nucleotide sequence databases [31,32,33] and six novel miRNAs have been identified by isolating and cloning of small RNA libraries [34]. Recently, Jeyaraj et al (2014) [35] analyzed expression and validation of several Camellia sinensis miRNAs in bud tissues by using the stem-loop pulse qRT-PCR method.…”
Section: Introductionmentioning
confidence: 99%